Konstruksi makna dan kuasa dalam wacana liputan6 tentang vadel badjideh: perspektif analisis wacana kritis van dijk - zubaidah, siti zubaidah (Maliki Interdisciplinary Journal, 2025)
This article discusses how meaning and power are constructed in a news story reported by Liputan6 entitled “Vadel Badjideh Sentenced to 12 Years in Prison, Family Prays and Surrenders to God” using Teun A. van Dijk's critical discourse analysis theory. This study focuses on three main aspects, namely text structure, social cognition, and social context. The results of the study show that the news emphasizes the family's story and aspects related to religion rather than legal explanations and the victim's perspective. Liputan6 depicts Vadel's family as submissive, religious, and compassionate, while the voices of the prosecutor and victim are not very dominant. This shows that there is a way of delivering news that attracts public sympathy and builds trust in God, while shifting attention away from legal aspects that are actually important. This study concludes that the media not only reports facts, but also helps build power relations and ideology through its choice of words, storytelling, and representation of the parties involved.